Technological Resources and the Direction of Corporate Diversification: Toward an Integration of the Resource-Based View and Transaction Cost Economics - Silverman, Brian S. (Management Science, 1999)
This study considers how a firm's resource base affects the choice of industries into which the firm diversifies. It offers two main extensions of prior research. First, it operationalizes technological resources at a more detailed level than in prior studies, thereby enabling a more stringent analysis of the direction of diversification. This analysis shows that the predictive power of the “resource-based view of the firm” is greatly improved when resources are measured at a finer level. Second, the study integrates principles from transaction cost economics into resource-based predictions concerning diversification. In particular, it tests the common assumption that rent-generating resources are too asset specific to allow contracting. The findings point to circumstances where resources can be and are exploited through contracting rather than through diversification.